MicroRNA-210-3p Targets RGMA to Enhance the Angiogenic Functions of Endothelial Progenitor Cells Under Hypoxic Conditions - Lu, Wen-Jing; Liang, Huai-Bin; Li, Yong-Fang; Tu, Xuan-Qiang; He, Ji-Rong; Ding, Kai-Qi; Yang, Guo-Yuan; Xin, Xiao-Yu; Zeng, Li-Li (Frontiers in Cellular Neuroscience, 2019)
Endothelial progenitor cells (EPCs) are multipotential stem cells considered to have immense clinical value for revascularization. However, the clinical application of EPCs has been hampered by their clinical potency in ischemic anoxic environments. This study aimed to explore the effect of microRNA-210 (miR-210) on EPCs under oxygen-glucose deprivation (OGD) conditions. We generated a model of EPCs cultured under OGD conditions to simulate ischemia and explore the expression of miR-210 in vitro. With longer exposure to hypoxia, we found that miR-210-3p expression was highly upregulated in OGD groups compared to that in controls from 4 to 24 h,but not miR-210-5p. We then transfected a miR-210-3p mimic and inhibitor into EPCs, and after 24 h, we exposed them to OGD conditions for 4 h to simulate ischemia. We detected miR-210 by real-time polymerase chain reaction (RT-PCR) and tested the proliferation, migration, and tube formation of normal EPCs and OGD-treated EPCs by CCK-8, transwell chamber, and Matrigel assays, respectively. The direct targets of miR-210-3p were predicted using miRWalk. Compared to that in normal EPCs, higher miR-210-3p expression was found in OGD-treated EPCs (p < 0.05). Moreover, upregulation of miR-210-3p was found to promote proliferation, migration, and tube formation in EPCs under normal and OGD conditions (p < 0.05), whereas down-regulation inhibited these abilities in OGD-treated EPCs (p < 0.05). Repulsive guidance molecule A (RGMA), a negative regulator of angiogenesis, was predicted to be a target of miR-210-3p. Accordingly, upregulation of miR-210-3p was found to inhibit its expression at the protein level in OGD-treated EPCs, whereas downregulation of miR-210-3p inhibited its expression (p<0.05). A dual-luciferase reporter system confirmed that RGMA is a direct target of miR-210-3p. MicroRNA-210-3p overexpression enhances the angiogenic properties of OGD-treated EPCs by inhibiting RGMA.